2016
DOI: 10.3389/fnagi.2016.00066
|View full text |Cite
|
Sign up to set email alerts
|

Exergame and Balance Training Modulate Prefrontal Brain Activity during Walking and Enhance Executive Function in Older Adults

Abstract: Different types of exercise training have the potential to induce structural and functional brain plasticity in the elderly. Thereby, functional brain adaptations were observed during cognitive tasks in functional magnetic resonance imaging studies that correlated with improved cognitive performance. This study aimed to investigate if exercise training induces functional brain plasticity during challenging treadmill walking and elicits associated changes in cognitive executive functions. Forty-two elderly part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
256
1
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 192 publications
(298 citation statements)
references
References 82 publications
14
256
1
7
Order By: Relevance
“…An overall reduction in connectivity to other circuits can occur in concert with an increase in connectivity within a highly localized circuit, and thus, result in a net decrease in regional metabolic demand. Our results are in line with recent work by Eggenberger et al who showed that 8 weeks of skilled motor training (dancing) compared to balance and stretching training elicits a greater reduction in PFC activation when subjects were imaged during a walking task using near infrared spectroscopy [8]. Our findings support the notion that the basal ganglia are significantly influenced by inputs from the PFC, which in the cognitive literature on executive function have been proposed to provide a top–down control signal for guiding the resolution of response competition that amplifies one response command and suppresses competing commands.…”
Section: Discussionsupporting
confidence: 92%
“…An overall reduction in connectivity to other circuits can occur in concert with an increase in connectivity within a highly localized circuit, and thus, result in a net decrease in regional metabolic demand. Our results are in line with recent work by Eggenberger et al who showed that 8 weeks of skilled motor training (dancing) compared to balance and stretching training elicits a greater reduction in PFC activation when subjects were imaged during a walking task using near infrared spectroscopy [8]. Our findings support the notion that the basal ganglia are significantly influenced by inputs from the PFC, which in the cognitive literature on executive function have been proposed to provide a top–down control signal for guiding the resolution of response competition that amplifies one response command and suppresses competing commands.…”
Section: Discussionsupporting
confidence: 92%
“…Training intensity was individually adapted to achieve a moderate to vigorous training level (Chodzko-Zajko, 2014). The time frame and training intensity was based on studies illustrating positive training effects in older adults performing a video game on a dance plate (Pichierri et al, 2012a; Law et al, 2014; Eggenberger et al, 2016) and on current recommendations for achieving physical fitness and fall prevention in elderly (Chodzko-Zajko, 2014). The participants trained in groups to enhance motivation and motor learning (Law et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Balance training performed with the help of video games that incorporate stepping exercises are effective in reducing falls next to improving gait and balance (Okubo et al, 2016). Furthermore, compared to conventional balance training this type of training differently modulates prefrontal brain activity and EFs (Eggenberger et al, 2016). It seems important, in this context, that interventions provide physical activity with decision-making opportunities because these are believed to facilitate the improvement of both motor performance and cognitive function (Yan and Zhou, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Seven studies used the Nintendo Wii exergaming system with a variety of software packages (Ackerman et al, 2010;Hughes et al, 2014;Maillot et al, 2012;Pompeu et al, 2011;Şimşek and Çekok, 2016;Staiano et al, 2012;Zimmermann et al, 2014), four used interactive dance games with pressure-sensitive dance platforms used to response to visual cues for foot movements (Eggenberger et al, 2016;Eggenberger, 2015;Schattin et al, 2016;Schoene et al, 2013), three used interactive cycling/treadmill training wherein participants completed various tasks or avoided obstacles while pedaling/walking around virtual tracks (AndersonHanley et al, 2016;Barcelos et al, 2015;Mirelman et al, 2016) one used virtual-reality kayaking requiring coordinated upper-body movement to navigate virtual lakes/rivers (Park and Yim, 2016), one used the Microsoft Kinect system to deliver an aerobic exercise routine (Kimhy et al, 2015), and one used interactive co-ordination training involving throwing/catching games in a virtual environment (Chan et al, 2010). Control conditions were waitlist/usual treatment (N=5), aerobic exercise (N=5), balance, stretching and strengthening exercises (N=4) and health education sessions, reading, cognitive remediation or memory training (all N=1).…”
Section: Included Studies and Participant Detailsmentioning
confidence: 99%